STRATEGI PEMULIHAN LAHAN GAMBUT OLEH TIM RESTORASI GAMBUT DAERAH (TRGD) DI PROVINSI RIAU - Dhea Mulia Sari; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The peatland restoration strategy is an effort made by the government to accelerate the recovery and restoration of the hydrological function of damaged peat. This is in accordance with Presidential Regulation No. 1 of 2016 concerning the Peatland Restoration Agency. In order to ensure the smooth implementation of the duties and functions of the Peatland Restoration Agency in the Riau Province, the Riau Province Regional Peat Restoration Team was formed, considering that Riau Province is one of the provinces that has become a priority for peatland restoration. Efforts have been made to restore peatlands through the 3R program, namely rewetting, revegetation and revitalization. With this program, it is hoped that it will be able to prevent and reduce the level of forest and peatland fires in Riau Province. The purpose of this study was to determine how the implementation of the peatland restoration strategy by the Regional Peatland Restoration Team in Riau Province and to find out the factors that hamper the implementation of the peatland restoration strategy by the Regional Peatland Restoration Team in Riau Province. This research uses purposive sampling technique with the type of qualitative research. using a descriptive approach and the required data both primary and secondary data obtained through observation, interviews, and documentation then analyzed based on research problems. The results of this study indicate that: first, the implementation of the peatland restoration strategy by the Regional Peat Restoration Team in Riau Province is still not optimal. Second, the inhibiting factor in implementing the strategy of the Riau Province Regional Peat Restoration Team in restoring peatlands is the lack of coordination and human resources. Keywords : Strategy, Peatland Restoration, Regional Peat Restoration Team (TRGD)